2019
DOI: 10.1109/access.2019.2945288
|View full text |Cite
|
Sign up to set email alerts
|

An Aggregated Model for Energy Management Considering Crowdsourcing Behaviors of Distributed Energy Resources

Abstract: Increasing deployment of distributed energy resources (DERs) is re-sculpturing the modern power systems in recent years. Future smart power distribution systems should be competent at accommodating extensive integration of DERs and managing the associated uncertainties at the distribution level. The electricity market has been proved to be an efficient way to employ market signals to direct behaviors of users and DERs with large capacity and homogeneous pattern. However, existing market frameworks cannot effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Fan et al [37] have analyzed the impact of RES into power system through demand response approach and presented the impact of demand response/comfort loss tolerance on integrated RES. Liang et al [38] have suggested an aggregated model for distributed energy management through crowd sourcing behaviors and validated the same by numerical studies by analyzing market performance and energy sharing.…”
Section: Based On Performance Evaluation and Its Implications Of Renewable Energy Integration In The Power System Networkmentioning
confidence: 98%
“…Fan et al [37] have analyzed the impact of RES into power system through demand response approach and presented the impact of demand response/comfort loss tolerance on integrated RES. Liang et al [38] have suggested an aggregated model for distributed energy management through crowd sourcing behaviors and validated the same by numerical studies by analyzing market performance and energy sharing.…”
Section: Based On Performance Evaluation and Its Implications Of Renewable Energy Integration In The Power System Networkmentioning
confidence: 98%
“…In Reference [67], a state feedback controller was proposed for the stabilization of an uncertain linear networked control systems with random communication time delays, which differs from the Lyapunov-Razumikh methodology. In Reference [68], a sufficient condition was obtained for the exponential stability of the networked systems, and they also the mentioned relationship between the dropout rate of the data-packets. An occurrence-based discrete-time model (an exponential unsure system with delay) was proposed by Reference [69] that showed that the stability of the projected system can be achieved by finding an effect for a switched stochastic system with an additive norm delimited uncertainty.…”
Section: Development Of Ncs Between 2001 To 2010mentioning
confidence: 99%
“…It is to be noted that the constraint on delays due to the network is not simple for some NCSs. So, to get rid of this constraint, efforts are created; see, e.g., References [49,68,88].…”
Section: A Switched System Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The load flexibility can change the trading offers. Other perspectives consider peak loads in the prosumer's vicinity with smart P2P subscribed capacity prices in [67], or the crowdsourcing concept for surplus energy planning or sharing, as is used in [68], or considering the indispensable local energy storage systems [69].…”
Section: Literature Reviewmentioning
confidence: 99%